Preparation and Characterization of Lanthanum Carbonate Octahydrate for the Treatment of Hyperphosphatemia - He, Anqi; Zhou, Fengshan; Ye, Fang; Zhang, Ying; He, Xiren; Zhang, Xin; Guo, Ran; Zhao, Xing; Sun, Yan; Huang, Ming; Li, Qin; Yang, Zhanlan; et al. (Journal of Spectroscopy, 2013)
We proposed a new approach to prepare lanthanum carbonate via reactions between lanthanum chloride and NaHCO3. In the reaction, small amount of NaHCO3 solution was firstly added to the acidic lanthanum chloride solution to generate lanthanum carbonate nuclei and then NaHCO3 is added to the lanthanum chloride at a constant speed. This approach makes both precipitation reaction and neutralization reaction take place simultaneously. Consequently, lanthanum carbonate is produced at low pH environment (pH below 4.0) so that the risk of generating lanthanum carbonate hydroxide is reduced. The product of the above reaction is validated by EDTA titration, elemental analysis, and XRD characterization. In addition, we established a FTIR spectroscopic method to identify La(OH)CO3 from La2(CO3)2·8H2O. Lanthanum carbonate exhibits considerable ability to bind phosphate.